Evaluating the psychometric properties of three WHO instruments to assess knowledge about human rights, attitudes toward persons with mental health conditions and psychosocial disabilities, and practices related to substitute decision-making and coercion in mental health - Moro, Maria Francesca; Gyimah, Leveana; Susser, Ezra; Ansong, Joana; Kane, Jeremy; Amissah, Caroline; Gureje, Oye; Osei, Akwasi; Norcini Pala, Andrea; Taylor, Dan; Drew, Nathalie; Kofie, Humphrey; et al. (Frontiers in Psychiatry, 2024)
Background Instruments to assess the knowledge about the rights of persons with mental health conditions and psychosocial disabilities, the attitudes toward their role as rights holders, and mental health professionals’ practices related to substitute decision-making and coercion are either missing or lack evaluation of their validity and reliability. Aim The aim of this study is to evaluate the validity and reliability of three instruments developed to fill this gap in the literature, the World Health Organization’s QualityRights (WHO QR) Knowledge questionnaire, the WHO QR Attitudes questionnaire, and the WHO QR Practices questionnaire. Methods A sample of participants was recruited and completed an online survey. Content validity and face validity were assessed for the three questionnaires. Based on the characteristics of the questionnaires, different approaches were used to assess their construct validity (confirmatory factor analysis, known group validity, and convergent and divergent validity). Internal consistency was evaluated using Cronbach’s alpha and test re-test reliability using Pearson’s and Spearman’s r coefficients. Results The analyses conducted indicate that the three questionnaires are valid and reliable instruments to evaluate the knowledge about the rights of persons with mental health conditions and psychosocial disabilities, the attitudes toward their role as rights holders, and mental health professionals’ practices related to substitute decision-making and coercion. Conclusion This finding lends support to the use of these instruments both within mental health services and in the general population for a better understanding of current knowledge, attitudes, and practices related to a human rights–based approach to mental health in mental health services and the community.